2015
DOI: 10.1152/physiolgenomics.00043.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of cyclic AMP response in bovine cumulus cells

Abstract: Khan DR, Guillemette C, Sirard MA, Richard FJ. Transcriptomic analysis of cyclic AMP response in bovine cumulus cells. Physiol Genomics 47: 432-442, 2015. First published June 16, 2015 doi:10.1152/physiolgenomics.00043.2015.-Acquisition of oocyte developmental competence needs to be understood to improve clinical outcomes of assisted reproduction. The stimulation of cumulus cell concentration of cyclic adenosine 3=5=-monophosphate (cAMP) by pharmacological agents during in vitro maturation (IVM) participates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
3
9
1
Order By: Relevance
“…The gene is also important to ROS regulation, as well as inhibition of apoptosis and proliferation [36,37]. However, in contrast with earlier work showing that cAMP modulators increased HK2 transcript levels [26], we found that the pre-IVM group had significantly lower HK2 expression than the MF group, regardless of PACAP treatment. Our results could be attributable differences in follicle size, culture period, and cAMP-modulator type, all factors that influence the effectiveness of HK2 as an apoptosis indicator.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The gene is also important to ROS regulation, as well as inhibition of apoptosis and proliferation [36,37]. However, in contrast with earlier work showing that cAMP modulators increased HK2 transcript levels [26], we found that the pre-IVM group had significantly lower HK2 expression than the MF group, regardless of PACAP treatment. Our results could be attributable differences in follicle size, culture period, and cAMP-modulator type, all factors that influence the effectiveness of HK2 as an apoptosis indicator.…”
Section: Discussioncontrasting
confidence: 98%
“…In mice, PACAP treatment during IVM improves cumulus expansion because PACAP contributes to cAMP response element-binding protein (CREB) phosphorylation through the cAMP/PKA pathway [21], and CREB is important to HAS2 expression [24,25]. Indeed, other cAMP modulators have generally increased HAS2 expression through the same pathway [26]. Moreover, cAMP-modulator treatment can immediately upregulate extracellular-matrix-formation genes during the pre-IVM stage, although effectiveness differs across modulator type [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial number and activity are also enhanced [10,22], which are additionally related to oocyte competence [26,27]. Lastly, cAMP-modulated IVM up-regulates genes involved in cell communication and metabolism, steroidogenesis and formation of extracellular matrix in cumulus cells [28], all of which are likely to reflect improved oocyte competence.…”
Section: Introductionmentioning
confidence: 99%
“…; Khan et al. ). These effects of cAMP might have augmented oocyte maturation, leading to better developmental competence.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been attributed to the prevention of spontaneous premature meiotic resumption and early degradation of cAMP by inhibiting PDE3A activity after CLZ treatment (Albuz et al 2010). Conversely, cAMP has been shown to be involved in steroidogenesis, cell metabolism and cumulus cell expansion during oocyte maturation through protein kinase A (Chen et al 2009;Khan et al 2015). These effects of cAMP might have augmented oocyte maturation, leading to better developmental competence.…”
Section: Discussionmentioning
confidence: 99%